Velocidade de semeadura e profundidade da haste em sistema plantio direto de milho e soja - Cavichioli, Fabio Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
No tillage is a reality in Brazilian agriculture, which is growing every year, modernization and study of the subject being required increasingly facing new aggregate machinery mechanisms. This system is characterized by less intensive tillage, and by reducing the frequency of agricultural machinery traffic on the ground, and remain on the surface of even greater amount of plant mass, which characterizes it as a conservationist. Crops of corn and soybeans have high yield potential and can reach high yields. The objective of this thesis to study the possible interaction between travel speeds of the tractor assembly / seeder and depths of the planter chisel tillage corn and soybeans. The experiment was conducted in the agricultural years 2010/11 and 2011/12 and was conducted in the area of Finance of Education, Research and Production, UNESP / Jaboticabal, the soil of the experimental area was classified as Typic typical Eutroferric The moderate clayey, with a 2x3 factorial conducted in a randomized block design with six treatments and four replications, for a total of 24 experimental plots of 300 m². The treatments consisted of two velocities of the tractor / seeder (4,5 and 6,5 km h-1), combined with three working depths of planter chisel fertilizer (10, 12,5 and 15 cm), for the sowing of corn and soybeans. The results showed that the variation in travel speed in the operation of maize sowing did not affect the longitudinal distribution of seedlings, initial stand, grain yield and demand for fuel. The tractor demanded greater power drawbar pull and power in the operation of sowing corn and soybeans when using the speed 6,5 km h-1, working with the depth 15 cm of the planter chisel. The use of higher travel speed of the tractor / seeder and set the working depth of the lower planter chisel provided less power demand set and trailed the same productivity of maize. The speed of 6,5 km h-1 ally working depth of 12,5 cm rods is indicated ...

O sistema plantio direto (SPD) é uma realidade na agricultura brasileira, que vem crescendo a cada ano, sendo necessário cada vez mais a modernização e estudo do tema, diante de mecanismos agregados às máquinas. Este sistema destaca-se pela menor intensidade de mobilização do solo, e pela redução da frequência de tráfego de máquinas agrícolas sobre o terreno, e por manter sobre a superfície do mesmo uma quantidade maior de massa vegetal, o que o caracteriza como conservacionista. Objetivou-se nesta tese estudar a possível interação entre velocidades de deslocamento do conjunto trator/semeadora-adubadora e profundidades das hastes sulcadoras na semeadura direta de milho e soja. O experimento foi instalado nos anos agrícolas de 2010/11 e 2011/12 e foi conduzido na área da Fazenda de Ensino, Pesquisa e Produção da UNESP/Jaboticabal-SP, com esquema fatorial 2x3 conduzido sob delineamento experimental em blocos casualizados, com seis tratamentos e quatro repetições, perfazendo um total de 24 parcelas experimentais de 300 m². Os tratamentos foram constituídos de duas velocidades de deslocamento do conjunto trator/semeadora-adubadora (4,5 e 6,5 km h-1), combinados com três profundidades de trabalho das hastes sulcadoras de adubo (10; 12,5 e 15 cm), para a semeadura da cultura do milho e da soja. Conclui que a variação na velocidade de deslocamento na operação de semeadura do milho não interferiu na distribuição longitudinal de plântulas, exceto os falhos, estande inicial, produtividade de grãos e na demanda de consumo de combustível. O trator exigiu maior força de tração na barra e potência na operação de semeadura do milho e da soja quando se utilizou a velocidade de 6,5 km h-1, trabalhando com a profundidade de 15 cm das hastes sulcadoras. A utilização da maior velocidade de deslocamento do conjunto trator/semeadora-adubadora e a menor profundidade de trabalho das hastes sulcadoras proporcionou menor ...
Keywords: Milho; Soja; Plantio direto; Mecanização agrícola; Desempenho; Máquinas agrícolas; Farm mechanization